Activation of spinal alpha-7 nicotinic acetylcholine receptor shortens the duration of remifentanil-induced postoperative hyperalgesia by upregulating KCC2 in the spinal dorsal horn in rats. Issue 1 (April 2017) - Gu, Wei; Zhang, Wei; Lei, Yishan; Cui, Yin; Chu, Shuaishuai; Gu, Xiaoping; Ma, Zhengliang
Background: Accumulating evidence has shown that the signal from spinal brain-derived neurotrophic factor/tyrosine receptor kinase B-K + -Cl − cotransporter-2 plays a critical role in the process of pain hypersensitivity. The activation of alpha-7 nicotinic acetylcholine receptors could have an analgesic effect on remifentanil-induced postoperative hyperalgesia. Nevertheless, whether intrathecal administration of PNU-120596, an alpha-7 nicotinic acetylcholine receptors selective type II positive allosteric modulator, before surgery could affect the duration of remifentanil-induced postoperative hyperalgesia remains unknown, and the effects of alpha-7 nicotinic acetylcholine receptors activation on the brain-derived neurotrophic factor/tyrosine receptor kinase B-K + -Cl − cotransporter-2 signal in the spinal dorsal horn of rats with remifentanil-induced postoperative hyperalgesia is still enigmatic. Results: We demonstrated that the brain-derived neurotrophic factor/tyrosine receptor kinase B-K + -Cl − cotransporter-2 signal played a critical role in the development of remifentanil-induced postoperative hyperalgesia. Intrathecal administration of PNU-120596 (8 µg/kg, 15 min before surgery) was associated with earlier signs of recovery from remifentanil-induced postoperative hyperalgesia. Simultaneously, remifentanil-induced postoperative hyperalgesia-induced K + -Cl − cotransporter-2 downregulation was partly reversed and coincided with a decreased expression of brain-derived neurotrophic factor/tyrosine receptor kinase B in the spinal dorsal horn, approximately correlating with the time course of the nociceptive behavior. Moreover, intrathecal administration of the K + -Cl − cotransporter-2 inhibitor VU0240551 significantly reduced the analgesic effect of PNU-120596 on remifentanil-induced postoperative hyperalgesia. Conclusions: The activation of alpha-7 nicotinic acetylcholine receptors induced a shorter duration of remifentanil-induced postoperative hyperalgesia by restoring the brain-derived neurotrophic factor/tyrosine receptor kinase B-K + -Cl − cotransporter-2 signal in the spinal dorsal horn of rats, which provides new insight into treatment in clinical postoperative pain management.